A real-world study to assess the disease control of moderate to severe atopic dermatitis in patients receiving dupilumab therapy, with atopic dermatitis control tool in Gulf countries - Amani Alfalasi; Ahmed Ameen; Atlal Al Lafi; Ayman El Gendi; Waqas Saad; Ahmed Ismail; Ayman Al Naeem; Srikumar Goturu; Nasser Al-Ahmed; Hussein Abdel Dayem; Arti Nanda; Amira Tawdy; et al. (Journal of Dermatological Treatment)
Purpose/aim of the study There is limited real-world evidence regarding the effectiveness and safety of dupilumab in Gulf countries. The study aimed to evaluate atopic dermatitis (AD) disease control in adult and adolescent patients (≥12 years) treated with dupilumab in Gulf countries.Materials and methods This observational study included patients with moderate-to-severe AD who initiated dupilumab within 30 days. Disease control, itching/pruritus, and patient satisfaction were assessed using Scoring Atopic Dermatitis (SCORAD), AD Control Tool (ADCT), and Patient Global Assessment of Treatment Effect (PGATE) scores at weeks 4, 12, and 24.Results The study included 187 participants with a mean age of 33.6 years. After 24 weeks, 75.1% of patients achieved disease control (ADCT score <7) compared to 4.3% at baseline (p < 0.001). Both ADCT and SCORAD scores significantly decreased from baseline scores (from 16.5 to 4.1 and 57.5 to 13.4, respectively, p < 0.001). Also, patient satisfaction improved significantly, with 65.3% reporting “Very Good” or “Excellent” PGATE scores in the 24th week compared to 20.3% at the baseline (p < 0.001). The limitations are the small number of included patients and the lack of long-term safety data.Conclusion In conclusion, Dupilumab therapy is effective in controlling symptoms of moderate-to-severe AD patients in the Gulf countries. Most patients achieved high disease control and satisfaction levels.